Physical activity during leisure time and primary prevention of coronary heart disease: an updated meta-analysis of cohort studies - Sofi, Francesco; Capalbo, Andrea; Cesari, Francesca; Abbate, Rosanna; Gensini, Gian Franco (European journal of cardiovascular prevention and rehabilitation, 2008)
A vast body of evidence during the last decades has shown the clear preventive role of physical activity in cardiovascular disease. The real magnitude of the association between physical activity during leisure time (LTPA) and primary prevention of coronary heart disease (CHD) has, however, not been completely defined. Meta-analysis of prospective cohort studies. Studies were included if they reported relative risks and their corresponding 95% confidence intervals (CI), for categories of LTPA in relation to CHD. The LTPA categories of the selected studies were grouped into three levels of intensity: high, moderate and low. The high level of physical activity was determined, to obtain a level of intensity attainable by the general population. Data were available for 26 studies, incorporating 513,472 individuals (20,666 CHD events), followed up for 4-25 years. Under a random-effects model, the overall analysis showed that individuals who reported performing a high level of LTPA had significant protection against CHD [relative risk 0.73 (95% CI 0.66-0.80), P<0.00001]. A similar significant protection against CHD, for individuals who practised a moderate level of LTPA, has been also demonstrated [relative risk 0.88 (95% CI 0.83-0.93), P<0.0001]. The current meta-analysis reports significant protection against the occurrence of CHD resulting from moderate-to-high levels of physical activity. These results strengthen the recommendations of guidelines that indicate the protective effect against cardiovascular disease of physical activity profiles that are attainable by ordinary people.